Micronutrient forgotten or missed in critically ill patients - Santiago Herrero (Indonesian Nutrition Association, 2023)
There is growing interest in the role of micronutrients (essential trace elements and vitamins) in optimizing health and in the prevention or treatment of some diseases. But we must not forget that micronutrients must also be considered in critically ill patients. There is a big difference.